Exploring Relationships Between Passion and Attitudes Toward Performance Enhancing Drugs in Canadian Collegiate Sport Contexts - Austin W. Wilson; Luke R. Potwarka (University of Kansas Libraries, 2015)
The purpose of this study was to explore relationships between passion and attitudes toward performance enhancing drugs (PEDs). Participants were 587 male and female varsity and coed intramural athletes from four Southern Ontario universities. Athletes completed the passion scale (Vallerand et al., 2003) and the performance enhancement attitudes scale (Petróczi, 2006). Full sample regression analyze revealed that higher scores on obsessive passion items were associated with more permissive attitudes toward PEDs (B =, 26, p < .001), while higher scores on harmonious passion items were associated with less permissive attitudes toward PEDs (B = -.29, p < .001). Moreover, obsessive passion emerged as a significant positive predictor of attitudes toward PEDs in all study contexts (i.e., coed recreational athletes, male/female varsity athletes). Implications for sport administrators, study limitations, and possible avenues for future research are discussed.